Changes in Peel and Pulp Characteristics of Banana (Musa AAA ‘William Cavendish’) as Influenced by Ripening Temperatures - Hashim, Shahida (2006)
A study on the changes in peel (colour, chlorophyll and carotenoid content, chlorophyll oxidase activity and chlorophyll derivatives) and pulp ripening characteristics (firmness, soluble solids concentration, titratable acidity and pH) of banana (Musa AAA ‘William Cavendish’) were conducted. Five mature green banana fingers per polystyrene tray were induced to ripen using 1000µl/L ethylene gas. Five banana fingers per tray were wrapped with a plastic cling-wrap film. The film was then injected with syringe to induced ripening against the fruits using 1000µl/L ethylene gas. Masking tape was then used to prevent the gas from moving out from the tray. The tray containing the banana fruits was then kept in a ripening chamber at 18±2 and 27±2 °C. After 24 hour, the film was removed and the fruit was allowed to continue ripening in respective temperatures until day five of ripening. The experiment was conducted using a randomized complete block design (RCBD) with a factorial arrangement of treatments (2 ripening temperatures x 6 ripening days) with five replications. Data from measurements of the peel (colour, chlorophyll and carotenoid contents, chlorophyll oxidase activity and chlorophyll derivatives) and pulp ripening characteristics were analyzed using analysis of variance (ANOVA) and regression were done using general linear model (GLM) (SAS Institute, Cary, N.C., 1989). Treatment differences were separated using Duncan multiple range test (DMRT). Correlation analysis by means of Pearson’s correlation matrix was performed to establish the associations between each parameter.